2012
DOI: 10.1097/ta.0b013e31822d233c
|View full text |Cite
|
Sign up to set email alerts
|

Electrical stimulation improves peripheral nerve regeneration in streptozotocin-induced diabetic rats

Abstract: Thus, the ES may improve the recovery of a severe peripheral nerve injury in diabetic animals, which could be considered as a supplementary treatment in diabetic neurotrauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…The published literature in the field of nerve regeneration in diabetes is limited and studies almost exclusively use streptozotocin-induced diabetes in rats in which blood glucose levels are high (see e.g. [1114]). The ability of axons to regenerate in relation to the state of the Schwann cells may also be an important point in relation to moderate blood glucose levels and in view of the global increase of diabetes, particularly bearing in mind its most common complication, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The published literature in the field of nerve regeneration in diabetes is limited and studies almost exclusively use streptozotocin-induced diabetes in rats in which blood glucose levels are high (see e.g. [1114]). The ability of axons to regenerate in relation to the state of the Schwann cells may also be an important point in relation to moderate blood glucose levels and in view of the global increase of diabetes, particularly bearing in mind its most common complication, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is very few evidence available to support this theory. In the previous literature, it has been reported that low frequency electroacupuncture and acupuncture could improve sciatica nerve regeneration [10, 12, 1517]. Koppes et al indicated that alternation of neurite growth could be manipulated by extracellular direct current [18].…”
Section: Discussionmentioning
confidence: 99%
“…Acupuncture and electroacupuncture provide a safe and effective way to help patients' rehabilitation after trauma accident. To the best of our knowledge, there are two pilot studies reported by Yao et al using the conduit tube to investigate the effects of electrical stimulation at different frequencies and current levels on regenerating sciatica nerves [10, 11]. Besides Bertelli's model, there was little literature available that described the rat's upper limb's nerve injury model and discussed the different nerve regeneration rates, especially for common diseases like median nerve injury [12].…”
Section: Introductionmentioning
confidence: 99%
“…The transplantation of adult neural stem cells (ANSCs) inside an autologous venous graft across a pig 30 mm long nerve gap in adult pigs induces axon regeneration and neurological function [294,295]. This is due to ANSCs increasing CNPase expression, indicating the activation of intrinsic Schwann cells [295].…”
Section: Tissue-engineered Nerve Graftsmentioning
confidence: 99%